1975
DOI: 10.1126/science.188.4187.472
|View full text |Cite
|
Sign up to set email alerts
|

Pioneer 11 Infrared Radiometer Experiment: The Global Heat Balance of Jupiter

Abstract: Data obtained by the infrared radiometers on the Pioneer 10 and Pioneer 11 spacecraft, over a large range of emission angles, have indicated an effective temperature for Jupiter of 125 degrees +/- 3 degrees K. The implied ratio of planetary thermal emission to solar energy absorbed is 1.9+/-0.2, a value not significantly different from the earth-based estimate of 2.5+/-0.5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…(2) (e.g., Ingersoll et al 1975, Guillot et al 1996. For β Pic b we calculate T eq ∼130 K, while the planet is much hotter at T eff ∼1700 K. This is in contrast to hot Jupiters which have effective temperatures close to their equilibrium temperatures (Cowan & Agol 2011).…”
Section: A Self-luminous Planetmentioning
confidence: 99%
“…(2) (e.g., Ingersoll et al 1975, Guillot et al 1996. For β Pic b we calculate T eq ∼130 K, while the planet is much hotter at T eff ∼1700 K. This is in contrast to hot Jupiters which have effective temperatures close to their equilibrium temperatures (Cowan & Agol 2011).…”
Section: A Self-luminous Planetmentioning
confidence: 99%
“…[Ingersoll et al, 1976], and analysis of Voyager measurements of thermal emission indicate the same [Pirraglia, 1984]. Ingersoll and Porco [1978] showed that the sum of internal heat flow and absorbed solar energy would be approximately independent of latitude if most of the poleward heat transport required to balance differential solar heating occurred in the deep interior of Jupiter rather than in just the several scale heights of atmosphere near cloud levels.…”
Section: Atmospheric Circulation and Dynamicsmentioning
confidence: 99%
“…3. Infrared emission at 45/ira wavelength, as observed by the infrared radiometer on the Pioneer 11 spacecraft (Ingersoll et aL, 1975b). See caption to Figure 2.…”
Section: Temperatures and Radiative Heat Fluxesmentioning
confidence: 99%
“…Most of the brightness temperature contrast is probably due to variable sources of opacity (clouds); the temperature differences at constant pressure are probably less than 2K. All of these temperature differences are small (Ingersoll et al, 1975b).…”
Section: Solar Vs Internal Energymentioning
confidence: 99%